Association of rs2651899 Polymorphism in the Positive Regulatory Domain 16 and Common Migraine Subtypes: A Meta‐Analysis - Lee, Hsun‐Hua; Chen, Chih‐Chung; Ong, Jiann‐Ruey; Lin, Yuan‐Feng; Lee, Fei‐Peng; Hu, Chaur‐Jong; Wang, Yuan‐Hung (Headache, 2020)
Background Migraine is a neurovascular disease with recurrent headache attacks. A polymorphism (rs2651899) of the PRDM16 gene, which is associated with migraine, was identified in recent genome‐wide association studies. The potential role of the PRDM16 rs2651899 polymorphism in migraine is still unknown. Therefore, we conducted this systematic review and meta‐analysis to examine this issue. Methods We performed a comprehensive literature search of the PubMed, Embase, and Google Scholar databases to identify eligible studies published before October 2018. Individual odds ratio and 95% confidence interval was used to estimate the pooled strength of the association between the PRDM16 rs2651899 polymorphism and common migraine subtypes, including migraine with aura (MA) and migraine without aura (MO). Results Six studies with 2853 cases and 9319 controls that fulfilled the inclusion and exclusion criteria were selected for this meta‐analysis. Of the 6 included studies, 4 studies had available data for MWA and another 4 studies had data for MWoA. Overall, significant migraine risks of 1.257, 1.305, and 1.419 were found under allele model (C vs T), dominant model (C/C+T/C vs T/T), and recessive model (C/C vs T/C+T/T), respectively. In the recessive model, significantly increased risks of 1.454 and 1.546 were found for MA and MO, respectively. Conclusion Our major findings suggest that PRDM16 rs2651899 polymorphism is associated with the risk of migraine. Furthermore, we found that PRDM16 rs2651899 polymorphism is significantly related to common migraine subtypes (MA and MO).